Endovascular Thrombectomy for Acute Ischemic Stroke Beyond 6 Hours From Onset: A Real-World Experience. Issue 7 (July 2020) - Casetta, Ilaria; Fainardi, Enrico; Saia, Valentina; Pracucci, Giovanni; Padroni, Marina; Renieri, Leonardo; Nencini, Patrizia; Inzitari, Domenico; Morosetti, Daniele; Sallustio, Fabrizio; Vallone, Stefano; Bigliardi, Guido; et al.
Abstract : Background and Purpose: To evaluate outcome and safety of endovascular treatment beyond 6 hours of onset of ischemic stroke due to large vessel occlusion in the anterior circulation, in routine clinical practice. Methods: From the Italian Registry of Endovascular Thrombectomy, we extracted clinical and outcome data of patients treated for stroke of known onset beyond 6 hours. Additional inclusion criteria were prestroke modified Rankin Scale score ⩽2 and ASPECTS score ≥6. Patients were selected on individual basis by a combination of CT perfusion mismatch (difference between total hypoperfusion and infarct core sizes) and CT collateral score. The primary outcome measure was the score on modified Rankin Scale at 90 days. Safety outcomes were 90-day mortality and the occurrence of symptomatic intracranial hemorrhage. Data were compared with those from patients treated within 6 hours. Results: Out of 3057 patients, 327 were treated beyond 6 hours. Their mean age was 66.8±14.9 years, the median baseline National Institutes of Health Stroke Scale 16, and the median onset to groin puncture time 430 minutes. The most frequent site of occlusion was middle cerebral artery (45.1%). Functional independence (90-day modified Rankin Scale score, 0–2) was achieved by 41.3% of cases. Symptomatic intracranial hemorrhage occurred in 6.7% of patients, and 3-month case fatality rate was 17.1%. The probability of surviving with modified Rankin Scale score, 0–2 (odds ratio, 0.58 [95% CI, 0.43–0.77]) was significantly lower in patients treated beyond 6 hours as compared with patients treated earlier No differences were found regarding recanalization rates and safety outcomes between patients treated within and beyond 6 hours. There were no differences in outcome between people treated 6-12 hours from onset (278 patients) and those treated 12 to 24 hours from onset (49 patients). Conclusions: This real-world study suggests that in patients with large vessel occlusion selected on the basis of CT perfusion and collateral circulation assessment, endovascular treatment beyond 6 hours is feasible and safe with no increase in symptomatic intracranial hemorrhage. Abstract : Supplemental Digital Content is available in the text.